The technique of listening, asking, and problem-solving on the application of Indonesian language teaching materials - Diah Latifah; Suci Sundusiah; Nuny Sulistiani Idris; Yulianeta Yulianeta; Yeti Mulyati; Isah Cahyani (Inovasi Kurikulum, 2024)
This research examines the power of listening, asking, and solving problems in training in using Indonesian language teaching materials for Indonesian language teachers for foreign speaker military officers. The problem identified is that Indonesian language teachers for foreign-speaker military officers must update their teaching materials according to student characteristics. Teaching materials need to be updated because there have been many changes in vocabulary, including the addition of several words in everyday life, including slang. The training participants are Indonesian language teachers who teach foreign-speaker military officers at Kementerian Pertahanan Republik Indonesia. The number of training participants was twenty people. Data analysis was carried out qualitatively and quantitatively. Qualitative research was carried out by interpreting the results of questions from training participants and quantitative quasi-experimental analysis to measure the influence of teaching materials training on understanding the use of Indonesian language teaching materials for foreign-speaker military officers. The research results showed that listening, asking, and solving problems succeeded in helping Indonesian language teachers who taught foreign-speaker military officers understand conceptually how to convey Indonesian language teaching materials to students.   Abstrak Penelitian ini mengkaji tentang kekuatan mendengarkan, bertanya dan memecahkan masalah dalam pelatihan penggunaan bahan ajar bahasa Indonesia bagi guru bahasa Indonesia bagi perwira militer penutur asing. Permasalahan yang teridentifikasi adalah guru bahasa Indonesia bagi perwira militer penutur asing harus memperbarui bahan ajarnya sesuai dengan karakteristik siswa. Bahan ajar perlu diperbarui karena banyak terjadi perubahan kosa kata, termasuk penambahan beberapa kata dalam kehidupan sehari-hari, termasuk bahasa gaul. Peserta pelatihan adalah guru bahasa Indonesia yang mengajar perwira militer penutur asing di Kementerian Pertahanan Republik Indonesia. Jumlah peserta pelatihan sebanyak dua puluh orang. Analisis data dilakukan secara kualitatif dan kuantitatif. Penelitian kualitatif dilakukan dengan interpretasi hasil pertanyaan peserta pelatihan dan analisis kuasi eksperimen kuantitatif untuk mengukur pengaruh pelatihan bahan ajar terhadap pemahaman penggunaan bahan ajar bahasa Indonesia bagi perwira militer penutur asing. Hasil penelitian menunjukkan bahwa mendengarkan, bertanya, dan memecahkan masalah berhasil membantu guru bahasa Indonesia yang mengajar perwira militer penutur asing memahami secara konseptual cara menyampaikan bahan ajar bahasa Indonesia kepada siswa. Kata Kunci: bahan ajar; pelatihan bahasa; pembelajaran berbasis masalah